2005
DOI: 10.1063/1.1856191
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of sharp change in magnetic hysteresis behavior of electrical steel at small plastic deformation

Abstract: In 2.2% Si electrical steel, the magnetic hysteresis behavior is sharply sheared by a rather small plastic deformation ͑0.5%͒. A modification to the Jiles-Atherton hysteresis model makes it possible to model magnetic effects of plastic deformation. In this paper, with this model, it is shown how a narrow hysteresis with an almost steplike hysteresis curve for an undeformed specimen is sharply sheared by plastic deformation. Computed coercivity and hysteresis loss show a sharp step to higher values at small str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…It can be shown that the residual strain e r is equal to the ''plastic'' strain given as e pl ¼ e À s=Y , where Y is Young's modulus and e is the total deformation produced by stress s. The relationship between the strain-hardening stress and the residual strain e r is phenomenologically given as Ludwik's law, which states that s À s y is equal to a constant multiplied by the residual strain e r to some power n, where n is known as the Ludwik exponent and is material-dependent, and hence is an irrational number and not necessarily a rational fraction. We have shown that the magnetic properties are a function of this relationship [3], and hence it would not be surprising if hysteresis loss also satisfies a Ludwik-like relationship. We shall show that indeed they do exhibit such a relationship, but not with the same exponent as shown by the mechanical behavior.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It can be shown that the residual strain e r is equal to the ''plastic'' strain given as e pl ¼ e À s=Y , where Y is Young's modulus and e is the total deformation produced by stress s. The relationship between the strain-hardening stress and the residual strain e r is phenomenologically given as Ludwik's law, which states that s À s y is equal to a constant multiplied by the residual strain e r to some power n, where n is known as the Ludwik exponent and is material-dependent, and hence is an irrational number and not necessarily a rational fraction. We have shown that the magnetic properties are a function of this relationship [3], and hence it would not be surprising if hysteresis loss also satisfies a Ludwik-like relationship. We shall show that indeed they do exhibit such a relationship, but not with the same exponent as shown by the mechanical behavior.…”
Section: Introductionmentioning
confidence: 91%
“…[2,3], except that n ¼ 0:66 is used now for the Ludwik exponent used in computing the strain-hardening stress that enters into the model. This value of n ¼ 0:66 was extracted from the tensile mechanical data after using nonlinear extrapolation from the uniform strain region to obtain the Sy used in Ludwik's law.…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2), in a pattern that has been shown to occur in non-oriented steels [1,2]: a large increase in losses after a very small straining (less than 1%) followed by a less steep linear increase in losses for larger strains. The differences between the behaviour shown in Figs.…”
Section: Resultsmentioning
confidence: 91%
“…The magnetic hardening after rolling may be described using an analogy to Ludwik 0 s description [2] of the mechanical hardening: P ¼ P 0 +ke n , where P are power losses, P 0 are power losses without a plastic deformation, k is an experimental constant and n is the hardening exponent. For rolling in RD, we have found n ¼ 0.34 and for rolling in TD, n ¼ 0.71.…”
Section: Resultsmentioning
confidence: 99%